Turning Back the Rising Sea: Theory performativity in the shift from climate science to popular authority. Issue 12 (December 2021) - Bowden, Vanessa; Gond, Jean-Pascal; Nyberg, Daniel; Wright, Christopher
Action on climate change continues to be hampered by vested interests seeding doubt about science and the need to reduce carbon emissions. Using a qualitative case study of local climate adaptation to sea level rise, we show how climate change science is translated into a self-referential theory focused on property prices. Our analysis develops two mechanisms – enablement and theorization – to explain the relationship between theory performativity and power within a process of translation. This contributes to (1) the performativity debate by showing how the constitution of power relations shapes theory performativity; (2) theories of power, by tracing the ways in which certain actors are able to enrol others and impact the authority of particular theories, and (3) processes of translation by developing mechanisms for following the ways in which power and theory performativity interact. We conclude by arguing that a performative understanding of how power shapes beliefs is central to combating the failure to address climate change.